8 Does the addition of a radial artery graft improve survival after higher risk coronary surgery? A Propensity-Score analysis. (9th June 2011) - Yap, C H; Hayward, P A; Shi, W Y; Dinh, D T; Reid, C M; Shardey, G C; Smith, J A
Abstract : Introduction: The use of the radial artery as a second arterial graft during coronary surgery has become popular due to high patency, encouraging clinical outcomes and low harvest site complication rates. However it is not clear whether higher risk patients derive such benefits. We sought to assess this by examining outcomes in higher risk subgroups. Methods: A multicentre database was analysed. From 2001 to 2009, 11 388 patients underwent isolated multivessel coronary surgery. We identified a higher risk subgroup (n=3149) according to emergent status, coronary instability, low ejection fraction, aortic counterpulsation or anticoagulant status. Among these, 2231 (71%) received at least 1 radial artery graft in addition to a left internal thoracic artery (LITA). The remaining 918 (29%) received LITA and veins only. Propensity-score matching and adjustment was performed to correct for group differences. Results: Patients who did not receive a radial artery were more likely to be older (mean age, radial: 66±10 years vs vein: 71±10, p<0.0001) female (22% vs 27%, p=0.002), have poor left ventricular function (16% vs 23%, p<0.0001), left main stenosis (35% vs 41%, p=0.002) or be of emergent status (11% vs 24%, p<0.0001). These patients experienced higher unadjusted 30-day mortality (2.2% vs 7.1%, p<0.0001) and poorer 7-year survival (p<0.0001). Furthermore, 548 patients in the radial group were propensity-score matched to 548 receiving LITA and veins. At 30 days, there were comparable rates of mortality (radial: 2% vs vein: 3%, p=0.19), stroke (1% vs 1%, p=0.51), myocardial infarction (1% vs 1%, p=0.77), major adverse cardiac or cerebrovascular events (MACCE) (2% vs 4%, p=0.12), return to theatre (5% vs 7%, p=0.19), hospital readmissions (12% vs 12%, p>0.99) and combined any mortality/morbidity (30% vs 32%, p=0.33). At 7 years, survival between radial and vein groups was similar (79±2.5% vs 80±2.5%, p=0.74). Propensity-adjusted multivariable regression did not show radial artery to be protective from 30-day mortality (p=0.14, OR 0.67, 0.40 to 1.13), 30-day MACCE (p=0.23, OR 0.76, 0.48 to 1.20), or mid-term mortality (p=0.79, HR 0.97, 0.78 to 1.20). Conclusions: This multicentre analysis suggests that patients with the greatest coronary instability, urgency of surgery, or impairment of ventricular function are not disadvantaged in the early and mid-term by use of a single arterial graft. Limitations include the inability to correct for unquantifiable variables retrospectively. Despite this, surgeons may utilise clinical judgement to select radial or venous conduits to supplement the LITA according to other patient factors or technical preference without prejudicing outcome.